Desire, Death and Sexual Politics in Gustave Flaubert’s Madame Bovary - Aminu Ahmed Nuru (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This paper examines the interface of desire, sexual politics and death through a literary-critical study of Gustave Flaubert’s Madame Bovary. The study focuses on the characterization of Emma which allows for a more in-depth and thorough exploration of her psychology vis-à-vis the concepts of desire and death. Firstly, the study extensively explores the Girardian models responsible for Emma Bovary’s desire within the novel. It brings out to the surface the models or mediators (such as romantic fictions, or fashion magazines, or the luxurious life of the rich) responsible for Emma’s desire. These mediators create a void or vacuum in Emma, which need to be filled. This, as the study has shown however, is difficult to do because of sexual politics. Flaubert here suggests that a woman’s desire ends only with death – a patriarchal creed that preordains woman to live without desire. Here, then, lies the intersection between Emma’s desiring pleasure and the instinct of death drive. Therefore, the study examines, from Jonathan Dollimore’s paradigm, the extent to which Emma Bovary’s desire, as portrayed by Girard, creates an “ideal” in her mind and causes her death. The implication of this is that a woman only ascertains a freedom from the trauma of unfulfilled desire in death, a tragic irony that surrounds Emma’s moment of departure from the world as a conscious being.